THE APPLICATION OF THE PRINCIPLE OF JUSTICE IN THE ENFORCEMENT OF HUMAN RIGHTS FROM THE PERSPECTIVE OF ISLAMIC LAW - Tazkiyah, Livia Nurul; Khirani, Lisa Rihana; Kurniati, Kurniati (ANAYASA : Journal of Legal Studies, 2026)
Human Rights are inherent and fundamental rights attached to every human being and must be respected, protected, and fulfilled. In the perspective of Islamic law, human rights are rooted in divine values, justice, humanity, and public welfare, aiming to safeguard human dignity in a comprehensive manner. This study aims to examine the essence of human rights from the perspective of Islamic law and its relevance within Indonesian society, analyze the mechanisms for the implementation and protection of Islamic human rights, and evaluate the impact of their implementation on social, legal, and constitutional life in Indonesia. This research employs a qualitative method with a library research approach and adopts a normative-philosophical framework by examiningprimary Islamic legal sources such as the Qur’an and Hadith, statutory regulations related to human rights, as well as relevant scholarly literature. The findings reveal that the concept of human rights in Islam is compatible with universal human rights principles and the Pancasila-based rule of law, particularly in upholding justice, equality, and respect for human dignity. The mechanisms for protecting Islamic human rights in Indonesia are implemented through the integration of Islamic values into the national legal system, the role of state institutions, religious courts, and civil society organizations. Furthermore, the implementation of Islamic human rights has contributed positively to strengthening social justice, protecting vulnerable groups, promoting religious tolerance, and improving public welfare. Therefore, the principles of justice in Islamic law play a strategic role in reinforcing human rights protection within Indonesia’s pluralistic society.